PEREMPUAN DAN ADAT PERKAWINAN (STUDI TENTANG MARGINALISASI PEREMPUAN DALAM JUJURAN ADAT ISTIADAT PERKAWINAN DI NIAS) - Efentinus Ndruru (Jurnal Community, 2017)
The study of gender studies (gender mainstreaming) today is a response to the phenomenon of domestic violence. Violence is inseparable from the dominance of men who are constructed in patriarchal culture. Women's research and marriage customs that impact on the marginalization of women in Nias is a continuous series of critics for gender observers, especially in the practice of marriage customs. There is a tendency of "women as purchased parties" to encourage the strengthening of arguments against acts of violence in the household. So in this case study, researchers dig information by conducting in-depth interviews, observations and literature review to find joints of violence that are not generally accepted. The results show that women in the marriage customary process are passive and not yet fully involved in the process of determining the marriage vows. The male side as a "buyer" with a considerable debt burden spawned a new problem that has an impact on wife violence. Therefore, it is necessary to socialize gender awareness as a means to oppose the maginalization experienced by women.Keyword: Gender, Nias, Maginalization, and Marriage Tradition.